Parasitological, serological and molecular evaluation of Trypanosoma vivax in cattle experimentally infected and early treated with isometamidium chloride in a region lacking the biological vector - Iuasse, Haryie Victória; Salvador, Vanessa Ferreira; de Morais, Igor Maciel Lopes; Leal, Luccas Lourenzzo Lima Lins; Couto, Luiz Fellipe Monteiro; Trindade, Artur Siqueira Nunes; Tamiozo, Gabriel Lopes; de Aquino, Lídia Mendes; Bastos, Thiago Souza Azeredo; Machado, Rosangela Zacarias [UNESP]; Ferreira, Lorena Lopes; Cadioli, Fabiano Antônio [UNESP]; et al. (Elsevier, 2025)
This study aimed to evaluate whether early treatment with isometamidium chloride (ISM) affects the production of anti-Trypanosoma vivax antibodies in cattle and whether it can induce parasitological cure, based on tissue analysis 546 days post-treatment in animals without evidence of parasitological relapse. Ten male cattle were experimentally infected with ≈ 1 × 106 viable T. vivax trypomastigotes (D-6) and treated with ISM six days post-infection (D0). The animals were euthanized 546 days post-treatment. During this period, the presence of T. vivax in blood was assessed using direct methods (Woo, Brener, and conventional PCR - cPCR) and serological analysis (indirect iELISA - iELISA). Liver, spleen, brain, heart and pre-scapular lymph node were collected and examined using cPCR. Molecular analysis of blood detected T. vivax DNA up to the day of treatment, but none thereafter. No T. vivax relapses in bloodstream was detected. Anti-T. vivax antibodies were detected from 42 to 546 days post-treatment, except in one animal. However, T. vivax DNA was still detected in the liver, brain, heart, and spleen of at least one animal at 546 days post-treatment. These findings suggest that early ISM treatment does not achieve complete parasitological clearance, as both antibodies and parasite DNA were detected.